IMPLEMENTASI UANG DIGITAL (E-MAAL) SEBAGAI UPAYA EFEKTIFITAS KEUANGAN SANTRI (STUDI DI PONDOK PESANTREN SIDOGIRI) - Zulmi, Nizar; Munir, Misbahul; Khusnudin, Khusnudin (ITB AAS Indonesia Surakarta, 2025)
The trend phenomenon of using electronic money in digital payments has become a step towards digital transformation in the field of finance. Easier, more transparent financial services that align with Islamic principles are driving Sidogiri Islamic boarding school to innovate with the goal of achieving the school's independence. This research aims to analyze the implementation of digital money (e-Maal) at Sidogiri Islamic boarding school and to assess its implementation effectiveness at Sidogiri Islamic boarding school. The method used is qualitative research by collecting data through observation, interviews, and direct fieldwork. The differences between this research and previous studies are the sample, implementation results, and detailed explanations related to the implementation as well as the effectiveness factors in its application. The research results show that the implementation of digital money (e-Maal) at Sidogiri Islamic boarding school began in 2017 and has continuously developed, showing effective results in its application. The implications of this research indicate that the implementation of digital money can also be applied to other Islamic boarding schools.